Evaluation of Entamoeba histolytica Acetyl Co-A Synthetase Recombinant Protein (rEhACS) for Serodiagnosis of Acute Amoebic Liver Abscess in Humans - Sith, Nur Shafiqa Md (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Amoebic liver abscess (ALA) caused by Entamoeba histolytica is the most common and potentially fatal extra-intestinal manifestation of amoebiasis. At Hospital Universiti Sains Malaysia (HUSM), diagnosis of ALA includes detection of antibodies using a commercial kit based on crude soluble antigens (CSA) of E. histolytica. CSA consist of a cocktail of E. histolytica proteins that are not well-defined in terms of the characteristics of the proteins and their masses. This study was done to evaluate the diagnostic potential of a well-defined recombinant protein of E. histolytica acetyl-Co-A synthetase (rEhACS) using serum samples from patients warded in HUSM who were diagnosed with ALA based on clinical symptoms, ultrasound imaging, and positive serology with commercial indirect haemagglutination kit, IHA (Cellognost® Amebiasis Kit, Dade Behring Marburg GmbH, Germany). The rEhACS was expressed in E. coli BL21 AI and purified using Ni-NTA resin column under optimized parameters. Presence of the purified rEhACS protein was ascertained based on observation of the prominently expressed -77 kDa on SDS-PAGE gel stained with Coomassie brilliant blue. The specificity and sensitivity of the purified protein were evaluated via enzymelinked immunosorbent assay (ELISA) using 30 ALA-positive serum samples and 30 ALA-negative serum samples with IHA seronegative obtained from patients infected with pathogens other than E. histolytica. The sensitivity and specificity for rEhACS/total anti-human IgG-ELISA were 500/o and 96.67% respectively. Meanwhile, for rEhACS/anti-human IgG4-ELISA were 36.67% and 96.67% respectively. In conclusion, this study demonstrated that rEhACS was highly specific for serodiagnosis of ALA. Interestingly, 50% (IgG-ELISA) or 36.6% (lgG4-ELISA) of the positive serum samples were probably obtained from patients with acute ALA. Future studies should focus on identifying new acute ALA cases based on rEhACS antigen followed by performing a battery of ALA examinations such as ultrasonography and molecular detection of biopsied liver abscess samples to confirm the infection.